Metaverse in the university and university in the metaverse: metaversity and multiversity - S. Khosravi (Taḥqīqāt-i Farhangī-i Īrān)
The online learning process during the recent Covid-19 pandemic gave us an input about the significance of technological requirements for improving learning experiences in long-distance education. Scanning textbook pages, typing course materials, playing videos of scientific experiments, asking students to record a vide while doing homework, discussions in the chat-box, and even using an interactive whiteboard in virtual classrooms are all examples of technologies used, but they are not unavailable or inaccessible cutting-edge technologies any more. Increasing students’ performance and satisfaction requires adoption and adaptation to other technologies. Therefore some schools and universities in Iran have been equipped with virtual reality (VR) and augmented reality (AR) hardware and software. Metaverse labs in some schools s well as universities have been launched; although its effectiveness is questionable. But the main question is if the metaverse is accessible to learning outside of academia, why do we need universities anymore? Is expansion of the metaverse synonymous with the reduction of the university? May universities use the metaverse in learning activities, but keeping their function to formal higher education? Will universities be transferred to (and transformed in) the metaverse? Will organizational structure (and social role) of universities change in the metaverse? Answering such questions wants us to reconsider the linguistic construct and the social relation of university, technology, and society - which needs returning to the conceptions and conceptualization of the university, turning points of great expectations for/from the university, and megatrends of socio-digital transformations. In this paper, we reviewed John Henry Newman’s idea of a university in its historical context, the discursive turn of higher education (HE) from university to Clark Kerr’s multiversity, and the resurgence of the idea of the metaverse (i.e. a single, universal, and immersive virtual world) as a consequence of pervasive prevalence of alternative technologies. Attempts are to re-articulate those concepts, draw a big picture of their social relations (in what Karl Popper called world 3), and provide an epistemological criticism of current debates on consistencies and controversies of university and the metaverse.